A randomized study on the effect of sequential acupoint stimulation on pulmonary function of patients with spontaneous pneumothorax during VATS perioperative period. Issue 10 (March 2019) - Sui, Tie-Quan; Zhang, Fa-Yue; Jiang, Ai-Ling; Zhang, Xiu-Qiang; Zhang, Zhi-Wei; Yang, Yang; Sun, Li-Ping
Abstract : Abstract: This study aims to explore the effect of sequential acupoint stimulation on the postoperative pulmonary function of patients with spontaneous pneumothorax who underwent video-assisted thoracoscopic surgery (VATS). Using a random number table, the patients were randomly divided into 2 groups: routine nursing group and sequential acupoint stimulation group. Patients in the routine nursing group received standard nursing care of thoracic surgery, while patients in the acupoint group received sequential acupoint stimulation on Shenshu (BL23), Gaohuang (BL43), Feishu (BL13), and Tiantu (CV22). Then, the maximal ventilatory volume (MVV), oxygen saturation (SpO2 ), postoperative drainage volume, postoperative drainage time, postoperative hospitalization days, and procalcitonin (PCT) were observed on the first, third, fifth and 30th day after VATS operation. On the fifth day after spontaneous pneumothorax was treated with VATS, MVV, and SpO2 of the sequential acupoint stimulation group were significantly higher than those of the routine nursing group ( P <  .05). On both the third day and fifth day after VATS, PCT of the sequential acupoint stimulation group was significantly lower than that of the routine nursing group ( P <  .01). Furthermore, the difference in postoperative drainage volume between the 2 groups was not statistically significant ( P >  .05), while chest tube drainage time ( P <  .01) and postoperative hospitalization days ( P <  .05) of the sequential acupoint stimulation group were significantly lower than those of the routine nursing group. In spontaneous pneumothorax patients who underwent VATS, sequential acupoint stimulation nursing was significantly more effective than routine postoperative nursing in promoting postoperative recovery of lung function, alleviating inflammatory response and shortening hospitalization days.